The value of x is
and
![x=(-1-√(37))/(12)](https://img.qammunity.org/2021/formulas/mathematics/middle-school/lotbswqv43de9j45feq5zyioc5ws7jukbw.png)
Explanation:
The equation is
![(1)/(x)-(2)/(3)=4 x](https://img.qammunity.org/2021/formulas/mathematics/middle-school/dw8vmrby0nqnbzk0tehtnzw4f9yskd80qq.png)
Subtracting by
on both sides,
![(1)/(x)-(2)/(3)-4 x=0](https://img.qammunity.org/2021/formulas/mathematics/middle-school/tmo54lg4ag0qpxjn7ue9i0uvlsjqyus4q0.png)
Taking LCM,
![(3-12 x^(2)-2 x)/(3 x)=0](https://img.qammunity.org/2021/formulas/mathematics/middle-school/5rdph1sk97cack9imi7dfu9vty2vn2io3p.png)
Multiplying by 3x on both sides,
![-12 x^(2)-2 x+3=0](https://img.qammunity.org/2021/formulas/mathematics/middle-school/zxtgmyu9qodn9vdran5jyr2hamkngh0bh1.png)
Dividing by (-) on both sides,
![12 x^(2)+2 x-3=0](https://img.qammunity.org/2021/formulas/mathematics/middle-school/bcvcn0fzy9gqh6qz5km8haet2ob4z6lg4g.png)
Using quadratic formula, we can solve for x.
![\begin{aligned}x &=\frac{-2 \pm \sqrt{2^(2)-4 \cdot 12 \cdot(-3)}}{2 \cdot 12} \\&=(-2 \pm √(4+144))/(2 \cdot 144) \\&=(-2 \pm √(148))/(24) \\&=(-2 \pm 2 √(37))/(24)\end{aligned}](https://img.qammunity.org/2021/formulas/mathematics/middle-school/mv8bpa93qr68puwj89f4ta8fkxx4hcgp83.png)
Taking out common term 2, we get,
![\begin{array}{l}{x=(-2(1 \pm √(37)))/(24)} \\{x=(-1 \pm √(37))/(12)}\end{array}](https://img.qammunity.org/2021/formulas/mathematics/middle-school/z0rqxhkh2msf53pc5dw4zq5880ndwyttjq.png)
Thus, the value of x is
and
![x=(-1-√(37))/(12)](https://img.qammunity.org/2021/formulas/mathematics/middle-school/lotbswqv43de9j45feq5zyioc5ws7jukbw.png)